Does Artisanal Tin Mining Affect Academic Performance of Secondary School Students?: A Case Study from Barakin Ladi Community in Plateau State, Nigeria - Nanya, Akperi,; Lasisi , Raimi (Research Developments in Arts and Social Studies Vol. 2, 2022)
The study looked at the topic of artisanal tin mining and secondary school pupils' academic performance in the mining community of Barakin-Ladi vs Mangu, a non-mining community in Plateau State, Nigeria. The study's main goal was to look into the differences in students' performance in secondary school terminal tests like WAEC/NECO and tertiary entrance examinations like JAMB/UTME in Barakin-Ladi and Mangu. Relevant data was retrieved from 732 respondents in the two LGAs to meet these goals. The Taro Yamane method was used to determine the sample size. The respondents, all of whom were secondary school students, were chosen using a simple random sampling technique from each of the two LGAs. The study collected data from both primary and secondary sources. The data was analysed using quantitative approaches (basic percentage and chi-square). When compared to Mangu, where strong academic achievement was documented in WAEC/JAMB examinations, the data demonstrated a relationship between social dangers such as child labour and mining-related conflicts and low student performance in Barakin-Ladi. These conclusions were supported by a comparison of historical WEAC and JAMB results from the two research locations. The study reports that among other things, community-wide education about the dangers of artisanal Tin mining to schoolchildren and the enforcement of artisanal Tin mining regulations in Barakin-Ladi.